Neuronal Ceroid Lipofuscinosis: The Multifaceted Approach to the Clinical Issues, an Overview - Simonati, Alessandro; Williams, Ruth E. (Frontiers in Neurology, 2022)
The main aim of this review is to summarize the current state-of-art in the field of childhood Neuronal Ceroid Lipofuscinosis (NCL), a group of rare neurodegenerative disorders. These are genetic diseases associated with the formation of toxic endo-lysosomal storage. Following a brief historical review of the evolution of NCL definition, a clinically-oriented approach is used describing how the early symptoms and signs affecting motor, visual, cognitive domains, and including seizures, may lead clinicians to a rapid molecular diagnosis, avoiding the long diagnostic odyssey commonly observed. We go on to focus on recent advances in NCL research and summarize contributions to knowledge of the pathogenic mechanisms underlying NCL. We describe the large variety of experimental models which have aided this research, as well as the most recent technological developments which have shed light on the main mechanisms involved in the cellular pathology, such as apoptosis and autophagy. The search for innovative therapies is described. Translation of experimental data into therapeutic approaches is being established for several of the NCLs, and one drug is now commercially available. Lastly, we show the importance of palliative care and symptomatic treatments which are still the main therapeutic interventions.